Genomic Variability of O Islands Encoding Tellurite Resistance in Enterohemorrhagic Escherichia coli O157:H7 Isolates - Taylor, Diane E. (American Society for Microbiology, 2002)
Strains of Escherichia coli causing enterohemorrhagic colitis belonging to the O157:H7 lineage are reported to be highly related. Fifteen strains of E. coli O157:H7 and 1 strain of E. coli O46:H(−) (nonflagellated) were examined for the presence of potassium tellurite resistance (Te(r)). Te(r) genes comprising terABCDEF were shown previously to be part of a pathogenicity island also containing integrase, phage, and urease genes. PCR analysis, both conventional and light cycler based, demonstrated that about one-half of the Te(r) E. coli O157:H7 strains (6 of 15), including the Sakai strain, which has been sequenced, carried a single copy of the Te(r) genes. Five of the strains, including EDL933, which has also been sequenced, contained two copies. Three other O157:H7 strains and the O46:H(−) strain did not contain the Te(r) genes. In strains containing two copies, the Te(r) genes were associated with the serW and serX tRNA genes. Five O157:H7 strains resembled the O157 Sakai strain whose sequence contained one copy, close to serX, whereas in one isolate the single copy was associated with serW. There was no correlation between Te(r) and the ability to produce Shiga toxin ST1 or ST2. The Te(r) MIC for most strains, containing either one or two copies, was 1,024 μg/ml, although for a few the MIC was intermediate, 64 to 128 μg/ml, which could be increased to 512 μg/ml by pregrowth of strains in subinhibitory concentrations of potassium tellurite. Reverse transcriptase PCR analysis confirmed that in most strains Te(r) was constitutive but that in the rest it was inducible and involved induction of terB and terC genes. Only the terB, -C, -D, and -E genes are required for Te(r). The considerable degree of homology between the ter genes on IncH12 plasmid R478, which originated in Serratia marcescens, and pTE53, from an E. coli clinical isolate, suggests that the pathogenicity island was acquired from a plasmid. This work demonstrates diversity among E. coli O157:H7 isolates, at least as far as the presence of Te(r) genes is concerned.